Digital Storytelling: An Effort to Empower Local Wisdom at SMA Sains Plus Tahfidz Qur’an Al-Ammar - Ningsih, Ayu Melati; Kristiana, Vera; Mayasari, Mayasari; Aprilia, Vira; Melani, Devi (Westscience Press, 2026)
This community service program aims to empower local wisdom through the implementation of digital storytelling at SMA Sains Plus Tahfidz Qur’an Al-Ammar, an Islamic boarding school integrating Qur’anic values, science education, and character development. The program addresses three main challenges; 1) the limited integration of local wisdom in learning, 2) students’ low academic storytelling skills, and 3) the absence of an integrated digital storytelling learning model. A participatory Project-Based Learning (PjBL) approach was employed, involving teachers and students in workshops, training, and mentoring focused on cultural literacy, storytelling techniques, and digital content production. The methods included needs analysis, capacity building, storytelling training, and the development of digital storytelling videos. The results demonstrate notable improvement in students’ understanding of local wisdom, storytelling competence, digital literacy, and creative expression. Key outputs include educational digital storytelling videos, a practical learning guide, and an integrated digital storytelling learning model. This program contributes to strengthening cultural identity, enhancing 21st century skills, and promoting sustainable, culturally responsive learning within Islamic secondary education.